Análisis de la interacción entre los determinantes de la ambigüedad causal: Especificidad, complejidad y carácter tácito - U. Planck Barahona (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
This work deepens on the base of Reed and DeFillippi's pattern (1990)-in the existing relationships among three characteristics that a resource must possess to generate causal ambiguity and to create barriers to imitation, that is, in the tacit character of knowledge, complexity of decisions and specificity of the resources. The conclusions of the work are lead to two propositions 1) the decisions of individual complex problems or collective are positively associated with the process of accumulation of the tacit knowledge and 2) the specificity of the assets is related directly to the complexity of the decisions-taking process. In essence, it is argued that the factors of complexity and tacit character can be partially analyzed depending upon the specific character the resource has.
Keywords: 330; resources and capabilities; tacit knowledge; complexity; specificity